1967
DOI: 10.1007/bf02901253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transesterification of lard on stability, antioxidant‐synergist efficiency, and rancidity development

Abstract: Glyceride rearrangement of lard did not affect its resistance to oxidation or alter the efficiency of antioxidants and synergists. Changes in stability were due to the decomposition of toeopherol and the formation of reducing substances. The position of unsaturated fatty acids in the glyeeride may influence the free v(flatile carbonyl compounds present in autoxidized lard and in rancidity development. Interesterifieation under vacuum produced an odorless and colorless randomized lard with natural stability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Raghuveer and Hammond (4) and Wada and Koizumi (5) found that increased unsaturated FA on carbon 2 increased TAG stability. Conversely, Zalewski and Gaddis (6) found that increase in unsaturated FA on carbon 2 decreased TAG oxidative stability. Other workers, e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Raghuveer and Hammond (4) and Wada and Koizumi (5) found that increased unsaturated FA on carbon 2 increased TAG stability. Conversely, Zalewski and Gaddis (6) found that increase in unsaturated FA on carbon 2 decreased TAG oxidative stability. Other workers, e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, TAG shows higher resistance to oxidation when docosahexaenoic acid exists at the sn-2 position than that at the sn-1(3) position [4]. In contrast, some reports indicated that TAG containing high amounts of UFA at the sn-2 position was susceptible to oxidation [5,6]. It was also reported that the positional distribution of UFA showed no effect on the oxidation of TAG [7].…”
Section: Introductionmentioning
confidence: 99%
“…From this, it might be expected that the stability of the triglyceride could be improved by shifting unsaturated fatty acids from the 1,3positions to the 2-position of glycerol. However, Zalewski and Gaddis (2) demonstrated that the oxidation of lard which was rich in triglycerides having unsaturated fatty acids linked at the 1,3-positions became faster after random interesterification. It is not certain whether the observations obtained with lard deny the abovementioned suggestion of Raghuveer and Jlammond, since the shift of unsaturated fatty acid from the 1,3-positions to the 2-position of glycerol in lard triglycerides with random interesterification was not confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%